Human NKT cells promote monocyte differentiation into suppressive myeloid antigen-presenting cells - Hegde, Subramanya (The Society for Leukocyte Biology, 2009)
NKT cells have been shown to promote peripheral tolerance in a number of model systems, yet the processes by which they exert their regulatory effects remain poorly understood. Here, we show that soluble factors secreted by human NKT cells instruct human peripheral blood monocytes to differentiate into myeloid APCs that have suppressive properties. NKT-instructed monocytes acquired a cell surface phenotype resembling myeloid DCs. However, whereas control DCs that were generated by culturing monocytes with recombinant GM-CSF and IL-4 had a proinflammatory phenotype characterized by the production of IL-12 with little IL-10, NKT-instructed APCs showed the opposite cytokine production profile of high IL-10 with little or no IL-12. The control DCs efficiently stimulated peripheral blood T cell IFN-γ secretion and proliferation, whereas NKT-instructed APCs silenced these T cell responses. Exposure to NKT cell factors had a dominant effect on the functional properties of the DCs, since DCs differentiated by recombinant GM-CSF and IL-4 in the presence of NKT cell factors inhibited T cell responses. To confirm their noninflammatory effects, NKT-instructed APCs were tested in an in vivo assay that depends on the activation of antigen-specific human T cells. Control DCs promoted substantial tissue inflammation; however, despite a marked neutrophilic infiltrate, there was little edema in the presence of NKT-instructed APCs, suggesting the inflammatory cascade was held in check. These results point to a novel pathway initiated by NKT cells that can contribute to the regulation of human antigen-specific Th1 responses.